2019
DOI: 10.1111/tri.13428
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of rejection after basiliximab induction in sensitized kidney transplant recipients without pre‐existing donor‐specific antibodies – a retrospective study

Abstract: Depleting induction therapy is recommended in sensitized kidney transplant recipients (KTRs), though the detrimental effect of nondonor-specific anti-HLA antibodies is not undeniable. We compared the efficacy and safety of basiliximab and rabbit anti-thymocyte globulin (rATG) in sensitized KTRs without pre-existing donor-specific antibodies (DSAs). This monocentric retrospective study involved all sensitized KTR adults without pre-existing DSAs (n = 218) who underwent transplantation after June 2007. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
0
16
3
Order By: Relevance
“…Surprisingly, the incidence of de novo DSA was high in their study: 15.8% in patients receiving rATG and 21.7% in patients receiving basiliximab. 6 The difference between our results and the Goumard et al 6 study may be explained by differences in the immunosuppression maintenance protocols as well as the levels and doses of immunosuppressants used in the 2 studies. The high incidences of acute rejection and de novo DSA in the Goumard et al 6 study can be related to a low maintenance immunosuppression.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Surprisingly, the incidence of de novo DSA was high in their study: 15.8% in patients receiving rATG and 21.7% in patients receiving basiliximab. 6 The difference between our results and the Goumard et al 6 study may be explained by differences in the immunosuppression maintenance protocols as well as the levels and doses of immunosuppressants used in the 2 studies. The high incidences of acute rejection and de novo DSA in the Goumard et al 6 study can be related to a low maintenance immunosuppression.…”
Section: Discussioncontrasting
confidence: 75%
“…Interestingly, the 5year follow-up of patients enrolled in the TAXI study indicates that despite the higher incidence of acute rejection in the daclizumab treatment arm, there was no significant difference in graft survival at the 5-year time point between the 2 treatment arms. 10 Goumard et al 6 reported a similar 4-year survival with induction therapies. In our study, patient survival and graft survival did not differ between the 2 treatment arms.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In this background comes the study from Goumard et al [14] published in this issue. The study tries to assess patients at intermediate risk (sensitized patients with anti-HLA antibodies but no donor specific antibodies DSA) and assess if IL2RA compared to ATG might provide similar efficacy (rejection and graft survival) and better safety (infection and malignancy).…”
mentioning
confidence: 99%